Mitigation of Ergot Vasoconstriction by Clover Isoflavones in Goats (Capra hircus) - Aiken, Glen E.; Flythe, Michael D.; Kagan, Isabelle A.; Ji, Huihua; Bush, Lowell P. (Frontiers in Veterinary Science, 2016)
Ergot alkaloids produced by a fungal endophyte (Epichloë coenophiala; formerly Neotyphodium coenphialum) that infects tall fescue (Lolium arundinaceum) can induce persistent constriction of the vasculature in ruminants, hindering their capability to thermo-regulate core body temperature. There is evidence that isoflavones produced by legumes can relax the vasculature, which suggests they could relieve ergot alkaloid-induced vasoconstriction and mitigate the vulnerability to severe heat stress in cattle that graze tall fescue. To test if isoflavones can relieve alkaloid-induced vasoconstriction, two pen experiments were conducted with rumen fistulated goats (Capra hircus) to determine with ultrasonograpy if isoflavones can 1) promote vascular compliance by countering alkaloid-induced vasoconstriction, and 2) relieve already imposed alkaloid-induced vasoconstriction. Goats were fed ad libitum chopped orchardgrass (Dactylis glomerata) - timothy (Phleum pratense) hay prior to conducting the experiments. Measures of carotid and interosseous luminal areas were obtained pre- (baseline) and post-ruminal infusions in both experiments with goats being fed the hay, and for blood flow rate in the carotid artery in Exp. 2. Responses to infusion treatments were evaluated as proportionate differences from baseline measures. Peak systolic velocity, pulsatility index, and heart rate were measured on the last day of treatment (DOT) in Exp. 1, and on all imaging sessions during Exp. 2. For Exp. 1, rumens were infused with ground toxic fescue seed and isoflavones in Phase A and with only the toxic seed in Phase B. The infusion treatments were switched between phases in Exp. 2, which employed a fescue seed extract having an ergot alkaloid composition equivalent to that of the ground seed used in Exp. 1. During Exp. 1, luminal areas of carotid and interosseous arteries in Phase A did not deviate (P > 0.1) from baselines over 1, 2, 3, and 4 DOT, but the areas of both declined linearly from baselines over 1, 2, 3, and 4 DOT in Phase B. By 6, 7, and 8 DOT in Exp. 2, luminal areas of the arteries and flow rate declined from baselines with infusions with the only seed extract in Phase A, but luminal areas and flow rate increased over 4, 5, and 6